The Natural Rate of Inflation - Engin Kara (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
I identify the natural rate of inflation: the threshold where signal-to-noise crosses unity. Extending Lucas (1972), I show that when inflation falls below sectoral volatility, firms cannot distinguish aggregate from idiosyncratic shocks. Sticky-price firms rationally filter out competitor price movements, creating endogenous stability. When inflation exceeds the natural rate, filtering ceases, coordination increases, and inflation becomes self-reinforcing. Using six million UK micro-price observations, I estimatethis threshold at 1.9%. Crossing it triggers a regime shift: price dispersion falls 10%, inflation persistence jumps from near-zero to 0.44, and monetary policy loses traction. These findings validate 2% targets as the limit of self-correction.
Keywords: E31; E52; E58; D21; L13; 330; inflation targeting; strategic pricing; behavioural thresholds; sectoral volatility; monetary policy; price complementarity